Association between tongue pressure and oral status and activities of daily living in stroke patients admitted to a convalescent rehabilitation unit - Shizuka Ninomiya; Wataru Fujii; Erika Matsumoto; Kiichiro Yamaguchi; Masao Hiratsuka (Wiley, 2024)
Abstract Background Clarifying how tongue pressure in convalescent stroke patients affects oral condition and activities of daily living (ADL) is important for developing oral rehabilitation programs and for rehabilitation care to reacquire ADL. Objective To clarify how tongue pressure is associated with oral status, ADL, and nutritional status in stroke patients. Methods Sixty‐eight patients aged 77.9 ± 10.0 years participated. The Japanese version of the Oral Health Assessment Tool was used to evaluate oral status. Data such as the ADL index functional independence measure (FIM), nutritional intake method, serum albumin, and body mass index were extracted from medical records. To examine factors associated with tongue pressure, multiple regression analysis was performed adjusting for confounding factors. The level of statistical significance was set at p < .05. Results In recovery phase stroke patients, tongue pressure was significantly lower in the total assistance group than in the partial assistance/independent group. In addition, tongue pressure was significantly lower in tube feeding patients than in oral feeding patients. FIM cognition score was an independent factor that had a significant effect on tongue pressure. Conclusion These findings suggest that ADL status also affects tongue pressure, thus patients' ADL including the FIM cognition subscale should also be evaluated while measuring tongue pressure.